Charcoal production from invasive Prosopis juliflora in Baringo County, Kenya - Koech, G.; Sola, P.; Wanjira, E.O.; Kirimi, M.; Rotich, H.; Njenga, M. (CIFOR-ICRAF, 2021)
This brief describes these results and offers recommendations for the use of invasive species for charcoal production.